Implementation of student experiential learning in health & wellbeing in a large university setting. (20th October 2021) - Heffernan, M; Mullins, B; Bermingham, AK; Neville, R; Dervan, N; Corish, CA; Murrin, CM; Fitzpatrick, P
Abstract: Background: Healthy UCD is a health promotion initiative in University College Dublin (UCD). Working together with university academic staff, we have provided opportunities for graded experiential learning for students in health and wellbeing-related courses. This abstract presents how experiential learning was implemented in the 2020/21 academic year. Objectives: The first objective was to provide a public health nutrition learning opportunity to MSc in Clinical Nutrition & Dietetics students through the design, implementation and evaluation of UCD Healthy Eating Week in Autumn 2020. Secondly, we aimed to facilitate the running of a wellbeing event by BSc Sport & Exercise Management students with Healthy UCD as their client in Spring 2021. The students had the additional challenge this year of delivering the content online. Results: MSc Clinical Nutrition & Dietetics students utilised Healthy UCD's website and social media channels to deliver a virtual Healthy Eating Week. Infographics, videos, articles and podcasts were produced which generated 1, 000 website visits and reached over 3, 000 on social media. Most students involved agreed that the event was successful (95%) and that they were sufficiently supported by Healthy UCD and their tutors (65%). BSc Sport & Exercise Management students devised and delivered a week-long event titled "Wellbeing Your Way", creating wellbeing seminars and live exercise classes with each receiving an average of 460 views. The students reported gaining valuable experience of the responsibilities of running a professional event and operating as a team. Conclusions: These examples of experiential learning for credit demonstrate how university campus health promotion teams can facilitate student learning and simultaneously reap the benefit for university faculty and students. The key requirements are committed academic engagement and supported students. Key messages: University campus health promotion provides excellent opportunities for experiential learning. Health promotion practical experience can have benefits both for students and for the university.